Association between outdoor light at night exposure and sleep problems in children and adolescents: a cross-sectional survey in Guangzhou city - Renshan HU; Yuxiu CHEN; Shuli XU; Guanghui DONG; Lebing WANG; Liwen HU (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo assess the correlation between exposure to outdoor light at night (LAN) and sleep problems in children and adolescents. MethodsCluster sampling was used to recruit a total of 34 751 participants aged 6 to 18 years from 37 primary and secondary schools in Guangzhou city, Guangdong province, between April and November 2017. Participants or their parents/caregivers were asked to complete a sleep disturbance scale for children developed by domestic researchers to evaluate sleep problems. Insufficient sleep duration was defined as less than 7 hours of daily sleep, while difficulty falling asleep was defined as a sleep-onset latency exceeding 45 minutes. Outdoor light at night (LAN) exposure based on Visible and Infrared Imaging Radiometer Suite Day/Night Band (VIIRS/DNB) satellite images was obtained using residential addresses. A generalized linear mixed-effects model with natural cubic spline curves was employed, using the minimum value of outdoor LAN exposure as reference, to explore the probability of sleep problems at different percentiles of outdoor LAN exposure among participants. Additionally, the modifying effects of age and gender on the relationship between outdoor LAN exposure and sleep problems were investigated. ResultsOf the 34 751 participants with valid responses, 7 184 (20.7%) reported insufficient sleep and 679 (2.0%) reported difficulty falling asleep. The average outdoor LAN exposure for participants was measured at 26.7 ±11.7 nW/cm2/sr. Compared to those with minimal outdoor LAN exposure levels, individuals exposed to higher levels (at the 95th percentile [P95]) had an increased likelihood of experiencing insufficient sleep (odds ratio [OR] = 1.54, 95% confidence interval [95%CI]: 1.27 - 1.87) as well as an increased likelihood of experiencing difficulty falling asleep (OR = 1.86, 95%CI: 1.19 - 2.91). The stratified analysis results revealed a significantly higher likelihood of insufficient sleep associated with outdoor LAN exposure in participants under the age of 12, compared to those aged 12 and above (OR [95%CI] for the LAN exposure at P5 : 1.50 [1.31 - 1.72] vs. 1.14 [1.07 - 1.21] and for the LAN exposure at P25 : 3.29 [2.15 - 5.06] vs. 1.61 [1.32 - 1.95].ConclusionThe association between outdoor LAN exposure and sleep problems in children and adolescents was found to be nonlinear and positively correlated, with a potentially stronger effect observed in younger children.